VR READY: a protocol for a non-randomised, single-arm, mixed methods, feasibility trial of a coproduced ViRtual REality intervention to AiD recoverY in people recently admitted to intensive care - Ceri Battle; Michelle Smalley; Kim Smallman; Paul Twose; Katherine Cullen; Ceri Lynch; Sarah Gill; Alys Irving; Cheney J G Drew; Craig Greenstock; Domonic White (BMJ Open)
Introduction Post-intensive care syndrome (PICS) describes a cluster of ongoing symptoms experienced by a large proportion of patients previously admitted to critical care. Despite a large rise in survival following critical care, interventions to support recovery and combat PICS are lacking. It has been suggested that the use of digital tools such as virtual reality (VR) may play a useful role in the development of recovery-supporting interventions. We engaged with people with lived experience of critical care admission to coproduce a VR intervention (ViRtual REality to AiD recoverY post ICU (VR READY)). Here, we present a protocol for the initial feasibility and acceptability testing of this intervention.Methods and analysis This is a single-arm, single-site, non-randomised feasibility trial of VR READY. Up to 25 participants recently admitted to critical care will be recruited to use the VR READY intervention for at least 5 min per day for a period of 14 days. Participants must have capacity to consent and be free from ongoing delirium in order to participate. Outcomes relating to sleep and well-being will be measured at baseline and at day 14 after intervention delivery. The primary outcome is feasibility, which will be assessed according to prespecified criteria. Participants will complete a qualitative interview to assess acceptability of the intervention, trial design and outcomes approximately 1 month after completing the intervention period. No formal statistical analysis of outcomes will be conducted, but these will be summarised descriptively. Interviews will be subjected to reflexive thematic analysis.Ethics and dissemination This study received a favourable ethical opinion by North-East York Research Ethics Committee (Ref 23/NE/0113) in June 2024. Study results will be disseminated through the peer review literature, ISRCTN registry and directly to participants, which will be facilitated by the study public and patient involvement steering group.Trial registration number ISRCTN88854487.